Potential Improvement of Pregnancy Outcome through Prenatal Small for Gestational Age Detection - Voskamp, Bart Jan; Beemsterboer, Daphne H.; Verhoeven, Corine J. M.; Rengerink, Katrien Oude; Ravelli, Anita C. J.; Bakker, Jannet J. H.; Mol, Ben Willem J.; Pajkrt, Eva (American Journal of Perinatology, 2014)
Objective To assess differences in mode of delivery and pregnancy outcome between prenatally detected and nonprenatally detected small for gestational age (SGA) neonates born at term.Study Design We performed a retrospective multicenter cohort study. All singleton infants, born SGA in cephalic position between 360/7 and 410/7 weeks gestation, were classified as either prenatally detected SGA or nonprenatally detected SGA. With propensity score matching we created groups with comparable baseline characteristics. We compared these groups for composite adverse perinatal outcome, labor induction, and cesarean section rates.Results We included 718 SGA infants, of whom 555 (77%) were not prenatally detected. Composite adverse neonatal outcome did not differ statistically significant between the matched prenatally detected and the nonprenatally detected group (5.5 vs. 7.4%, odds ratio [OR] 0.74, 95% confidence interval [CI]: 0.30–1.8). However, perinatal mortality only occurred in the nonprenatally detected group (1.8% [3/163] in the matched cohort, 1.3% [7/555] in the complete cohort). In the propensity matched prenatally detected SGA group both induction of labor (57 vs. 9%, OR 14.0, 95% CI: 7.4–26.2) and cesarean sections (20 vs. 8%, OR 2.9, 95% CI: 1.5–5.8) were more often performed compared with the nonprenatally detected SGA group.Conclusion Prenatal SGA detection at term allows timely induction of labor and cesarean sections thus potentially preventing stillbirth.
Keywords: small for gestation; prenatal detection; neonatal death; fetal death; induction of labor; propensity score